Vulnerability to HIV/AIDS in married heterosexual people or people in a common-law marriage - Guilhem, Dirce (2008)
OBJECTIVE: To study knowledge, preventive behavior, and perception regarding HIV/AIDS of heterosexual men and women that are married or in a common-law marriage. METHODS: Exploratory study carried out in the Federal District of Brazil, between 2001 and 2002. Heterosexual men and women (N=200) aged 18 and 49, married or in a common-law marriage were divided into two groups: (I) 50 couples approached in public places, and (II) 100 users of a Basic Health Unit, 50 were women and 50 were men. The instrument for data collection was a semi-structured questionnaire on demographic, socioeconomic and behavioral characteristics of the interviewees, with 38 questions, two of which were open. RESULTS: The age distribution between the groups was similar, but group I had a higher level of schooling and income, while group II had less knowledge about the ways that HIV is transmitted. The use of condoms was equally mentioned by both groups as one of the types of prevention. Of the interviewees, 14% reported its regular use in the last year. The main reasons for not using condoms were “trusting the partner” and “being incompatible with having a fi xed partner”. The perception of the risk of infection was more frequent among women. CONCLUSIONS: The population studied was vulnerable to the risk of getting the disease, although the interviewees had enough knowledge on HIV/AIDS. Their perceptions of the couple refl ected their acculturation in relation to gender roles and the hierarchization of the affective-sexual relationship, which can contribute to the small adoption of preventive behavior.